Prenatal diagnosis of a case with tetrasomy 9p confirmed by cytogenetics, FISH, microarray analysis and review - Gizem Kok Kilic; Erhan Pariltay; Emin Karaca; Burak Durmaz; Huseyin Ekici; Metehan Imamoglu; Firat Okmen; Haluk Akin; Ozgur Cogulu (Elsevier, 2022)
Objective: Tetrasomy 9p is a rare fetal condition. Cases are usually mosaic. Here, we present a non-mosaic tetrasomy 9p case with cytogenetic analysis, fluorescence in situ hybridization, microarray data, ultrasound findings, and phenotypic presentation. Case report: A pregnancy was referred to cytogenetic analysis because of increased nuchal translucency in prenatal ultrasound at 13 weeks of gestation. Prenatal laboratory analysis revealed an extra marker chromosome with a non-mosaic pattern. Ultrasonographic findings were unilateral cleft lip and palate, micrognathia, and atrioventricular septal defect at the 17th week; additionally, ventriculomegaly, left axis deviation of the fetal heart, and a single umbilical artery were determined at the 23rd week. Conclusion: Phenotypic severity in non-mosaic tetrasomy 9p widely differs depending on the chromosomal content. We recommend performing appropriate genetic tests in those pregnancies with the suspicion of tetrasomy 9p, evaluating the mosaic state, and following those cases with detailed ultrasonographic examinations.